Penyusunan Peraturan Desa Tentang Desa Wisata di Desa Peninjoan, Bangli - I Gusti Bagus Suryawan; I Nyoman Sutama; I Wayan Arthanaya; I. A. Wulan Prawesti; Klaustra Adhi Permana (Universitas Warmadewa, 2022)
The Review Village has great potential to be developed as a Tourism Village. In the development of tourist villages in the Desa Peninjauan, it has not been supported by legal rules governing the governance of tourist villages. Whereas legal certainty is very important in the development of Tourism Villages in Peninjoan Village, Tembuku District. This PKM aims to realize village regulations governing tourist villages in the Review Village. The form of activities carried out is technical guidance and assistance in drafting Village Regulations concerning Tourism Villages in Peninjoan Village, Tembuku District. The results of the PKM are in the form of a draft Village Regulation on tourist villages. PKM outputs consist of legal products of tourist village regulations, publications in scientific journals, and video documentation of activities.